2004
DOI: 10.1196/annals.1331.002
|View full text |Cite
|
Sign up to set email alerts
|

Discovery, Characterization, and Significance of the Cytochrome P450 ω‐Hydroxylase Pathway of Vitamin E Catabolism

Abstract: Tocopherols are known to undergo metabolism to phytyl chain-shortened metabolites excreted in urine. We sought to characterize the pathway, including associated enzymes, involved in this biotransformation. We previously found that human hepatoblastoma (HepG2) cultures metabolized tocopherols to their corresponding short-chain carboxychromanols. Putative metabolites of gamma-tocopherol that contained intact chromanol moieties were structurally identified using HepG2 cultures and electron impact gas chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 13 publications
(14 reference statements)
1
40
0
Order By: Relevance
“…1). On the other hand, the pathway of the ␣-and ␥-tocopherol metabolism to ␣-and ␥-CEHC involveshydroxylation of phytyl chains and the following ␤-oxidation, and the rate-limiting step is -hydroxylation by cytochrome P450 (CYP) 4F (10,22).…”
Section: Resultsmentioning
confidence: 99%
“…1). On the other hand, the pathway of the ␣-and ␥-tocopherol metabolism to ␣-and ␥-CEHC involveshydroxylation of phytyl chains and the following ␤-oxidation, and the rate-limiting step is -hydroxylation by cytochrome P450 (CYP) 4F (10,22).…”
Section: Resultsmentioning
confidence: 99%
“…The initial step of ␣-tocopherol degradation is a w-hydroxylation of the side chain element by cytochrome P450 hydroxylases. 54,55 Supplementation with ␣-tocopherol increases cytochrome P450s levels in mice 12,56 and activates the nuclear pregnane X receptor, 57 which itself regulates many genes linked to xenobiotic detoxification, including several P450 enzymes. 58 It is feasible that ␣-tocopherol is initially metabolized as a xenobiotic, perhaps explaining why previous studies generally only observe a life span extension when supplementation is initiated early in life.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these, there are further contradictory findings. Parker et al [171] emphasized that the hypothesis of involvement of CYP3A4 in the metabolism of vitamin E is only based on the assumption of ketoconazole specificity, which proved incorrect [172] . Testing recombinant human CYP3A4 in insect cell derived microsomes revealed no activity towards α-or γ-TOH [140] , whereas a systematic screening of other CYP enzymes showed tocopherol-ω-hydroxylase activity only for CYP4F2 [171] (for further details, see the section on CYP4F2 in chapter "metabolism of vitamin E").…”
Section: Cyp3a4mentioning
confidence: 99%
“…Parker et al [171] emphasized that the hypothesis of involvement of CYP3A4 in the metabolism of vitamin E is only based on the assumption of ketoconazole specificity, which proved incorrect [172] . Testing recombinant human CYP3A4 in insect cell derived microsomes revealed no activity towards α-or γ-TOH [140] , whereas a systematic screening of other CYP enzymes showed tocopherol-ω-hydroxylase activity only for CYP4F2 [171] (for further details, see the section on CYP4F2 in chapter "metabolism of vitamin E"). In addition, Birringer et al [120] showed that production of γ-CEHC from γ-TOH was not affected by rifampicin in HepG2 cells, leading to the conclusion that either CYP3A4 may not degrade all vitamin E forms to the same extent or other CYP enzymes may be involved in γ-TOH metabolism.…”
Section: Cyp3a4mentioning
confidence: 99%
See 1 more Smart Citation